Multimedia Interaktif dalam Pembelajaran Konsep Listrik bagi Calon Guru - Gunawan Gunawan; Ahmad Harjono; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
There are many abstract concepts in physics. This raises its own difficulties in learning physics. The difficulty in teaching abstract concepts can be solved using computer technology. Computer technology presents opportunities for learning abstract concepts, such as through the use of interactive multimedia in learning physics. In this study has developed an interactive multimedia on the concept of electricity. This study aims to examine the impact of the use of interactive multimedia on student mastery of the concept of electricity. The results showed an increase in mastery of concepts in both classes. The highest increase occurred in the concept of Coulomb's law, which is 68.6% (experimental group) and 48% (control group). Mastery electric concept experimental group is greater than the control group, indicates that interactive multimedia effective in supporting the process of learning physics.ÃÂ